TRADISI KATOBA: KEARIFAN LOKAL MASYARAKAT MUNA SEBAGAI UPAYA PENCEGAHAN KEKERASAN SEKSUAL TERHADAP ANAK DI KOTA KENDARI - Rivi Handayani; La Ode Sahidin; Sitti Haerani Idrus (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2017)
This study offers a method based on local wisdom of Muna society in Kendari City. When the children enter the age of 7-12 years, parents are required to organize Katoba rituals. Katoba ritual is a means to deliver and guide the child into the early phase of adult life. The content of the values in the katoba becomes the basic of early age, adult, even to the old age. Starting from the age of the children (after doing the ritual of katoba) until he is mature, then he has immoral acts, sentences that come out from the society "mina namandehao ihino katoba, datumobae tora datumoba" (he doesn’t know the essence of katoba, so he should do a “Toba” again). When the language that is coming from the society related to his action, it means that his action is an expression of insult to the immoral perpetrators. This research is a qualitative research. It was done by using ethical and emic approach. This method deals with the handling of sexual violence taken from the point of view of the society and the author's interpretation.